Spartina alterniflora has the highest methane emissions in a St. Lawrence estuary salt marsh - Comer-Warner, Sophie; Ullah, Sami; Ampuero Reyes, Wendy; Krause, Stefan; Chmura, Gail L (Environmental Research: Ecology, 2022)
Publication associated with dataset 'Methane fluxes from four elevation zones in a St. Lawrence Estuary salt marsh' (https://doi.org/10.5281/zenodo.6500188) funded under the European Union's MarieSkłodowska–Curie Action project number838296 MarshFlux: The effect of future global climate and land-use change on greenhouse gas fluxes and microbial processes in salt marshes. Salt marshes have the ability to store large amounts of 'blue carbon', potentially mitigating some of the effects of climate change. Salt marsh carbon storage may be partially offset by emissions of CH 4 , a highly potent greenhouse gas. Sea level rise and invasive vegetation may cause shifts between different elevation and vegetation zones in salt marsh ecosystems. Elevation zones have distinct soil properties, plant traits and rhizosphere characteristics, which affect CH 4 fluxes. We investigated differences in CH 4 emissions between four elevation zones (mudflat, Spartina alterniflora, Spartina patens and invasive Phragmites australis ) typical of salt marshes in the northern Northwest Atlantic. CH 4 emissions were significantly higher from the S. alterniflora zone (17.7 ± 9.7 mg C m −2 h −1 ) compared to the other three zones, where emissions were negligible (<0.3 mg C m −2 h −1 ). These emissions were high for salt marshes and were similar to those typically found in oligohaline marshes with lower salinities. CH 4 fluxes were significantly correlated with soil properties (salinity, water table depth, bulk density and temperature), plant traits (rhizome volume and biomass, root volume and dead biomass volume all at 0–15 cm) and CO 2 fluxes. The relationships between CH 4 emissions, and rhizome and root volume suggest that the aerenchyma tissues in these plants may be a major transport mechanism of CH 4 from anoxic soils to the atmosphere. This may have major implications for the mitigation potential carbon sink from salt marshes globally, especially as S. alterniflora is widespread. This study shows CH 4 fluxes can vary over orders of ...